Features of patients with advanced EGFR-mutated non-small cell lung cancer benefiting from immune checkpoint inhibitors - Chen, Qian; Shang, Xiaoling; Liu, Ni; Ma, Xinchun; Han, Wenfei; Wang, Xiuwen; Liu, Yanguo (Frontiers in Immunology, 2022)
Background Although immune checkpoint inhibitors (ICIs) generally show poor therapeutic efficacy in patients with epidermal growth factor receptor (EGFR) mutations, certain research indicate that a small proportion of these patients do respond to ICIs. The present study sought to identify the features of patients with EGFR mutations who might benefit from ICIs from multiple studies and discussed the optimal treatment paradigm for advanced non-small cell lung cancer (NSCLC) patients with EGFR mutations. Methods The profiles of 114 advanced NSCLC patients with EGFR mutations who received ICIs treatment were retrospectively reviewed. EGFR subtypes, programmed cell death ligand 1 (PD-L1) expression, and clinical characteristics regarding their impact on the efficacy of ICIs were investigated. Results Patients with major EGFR mutations (L858R or 19Del) had a shorter progression-free survival (PFS) and a lower objective response rate (ORR) as compared to patients with rare (20ins or G719X) and other EGFR mutations. Although not statistically significant, median overall survival (OS) tended to be longer in patients with negative (<1%) PD-L1 expression than with positive (≥1%) PD-L1 expression (15.61 vs. 7.40 months, p = 0.138). Median PFS and OS were significantly shorter in heavily treated patients (prior lines of therapy ≥3 lines vs. <3 lines: mPFS, 1.80 vs. 2.50 months, p = 0.003; mOS, 6.70 vs. 14.00 months, p = 0.031). ORR was also lower in patients who had received ≥3 prior lines of therapy compared to in those <3 prior lines of therapy (0.00% vs. 21.67%, p = 0.002). Conclusion Patients with major EGFR mutations showed poorer responses to ICIs than those with rare EGFR mutations. EGFR-mutated patients with lower PD-L1 expression showed a trend towards a longer OS after receiving ICIs. ICIs should be administered as early as possible to previously treated EGFR-mutated NSCLC patients. ICI-based combined therapies may be a direction for treatment of these patient subtypes in the future.